Residential Drainage System Planning X Sidoarjo District - Maulana, Akmal Dzikri; Setyowati, Rr Diah Nugraheni; Utama, Teguh Taruna (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
An increase in the population growth rate leads to a rise in the need for housing. Housing development can reduce water catchment areas, potentially leading to increased flooding. This drainage system planning aims to determine the flood discharge and channel capacity. The hydrological analysis employs the Gumbel distribution method to determine rainfall with return periods of 5 and 2 years. Rainfall for the 2- and 5-year return periods is equal to 109.5 mm/hr and 136.8 mm/hr. Furthermore, the hydraulic analysis for channel drainage capacity uses the continuity equation and SWMM 5.2 modeling. The results of the hydraulic analysis showed that the channel capacity can accommodate the flood discharge. This is reinforced by the modeling results, which state that the whole conduit and junction can accommodate the flood discharge. This is based on the simulation results of channel conduits that are not red. The channel conduit is marked with green, blue, and yellow markings. This indicates that the planned channel has complied with planning rules. Based on the results of research and planning of the residential drainage system in X Sidoarjo Regency, it can be concluded that the drainage channel plan’s capacity is sufficient to accommodate flood discharge. This is based on mathematical calculation results and modeling simulation results from the SWMM (Storm Water Management Model).